(untitled) (Al-Academy, 2022)
The theater benefited from the concept of (hypertext) to create different virtual worlds. The four chapters of the research included the first (methodological framework), the second (theoretical framework) came in two sections (hypertext, its concepts and applications) and (hypertextual space in theatrical performance), and the investigations resulted in indicators, including:1- Hypertext is interacting interactively, but it is organized by correlation as a basic feature that defines it with different manifestations.2- The hypertext combines the word with other formative elements that reduce a set of tagged information (word, image, light, shadow, color, number).In the third chapter (research procedures) (Lord play) was chosen as a sample intended for the research, and the fourth chapter contained the results and conclusions to reach the sources and references and the summary in English